Improving English Writing Skills Through Making a Poster by Canva to Seventh Grade Students at SMP Negeri 2 Tabanan - I Gede Gita Wiastra; IDA AYU OKA PURNAMI; NI KADEK INTAN ARIENSA; I GEDE BAGUS WISNU BAYU TEMAJA; NI KADEK AYU KARTIKA SEPTIANA (Wacana : Majalah Ilmiah Tentang Bahasa, Sastra Dan Pembelajarannya, 2025)
This study aims to improve the English writing skills of seventh-grade students at SMP Negeri 2 Tabanan through the use of Canva in creating descriptive posters. Writing is a crucial skill in language learning, as it allows learners to express ideas and thoughts in written form. However, many students face difficulties in writing, especially in constructing descriptive texts. Common errors found include grammar, spelling, punctuation, and sentence structure. This research employs a Classroom Action Research (CAR) method conducted in several cycles involving planning, action, observation, and reflection. Canva, a graphic design platform, is integrated as a learning medium to assist students in developing descriptive texts into visually engaging posters. Data were collected through pre-tests and post-tests as well as student questionnaires to assess their responses toward the use of Canva. The results showed a significant improvement in students’ writing skills, with the average score increasing from 65 in the pre-test to 78 in the post-test. Furthermore, students reported higher motivation and enthusiasm in the learning process. The use of Canva allowed students to be more creative, expand their vocabulary, and pay closer attention to language mechanics while writing. Therefore, Canva can serve as an effective tool to enhance English writing instruction in junior high schools.